Sumbangan Pendekatan Antropologi Hukum terhadap Pengkajian Wanita (Suatu Pengalaman Penelitian mengenai Peranan Wanita Batak Toba dalam Upaya Menyelenggarakan Kesejahteraan Sosial) - Sulistyowati Irianto (Antropologi Indonesia, 1992)
This article had the aim to show in what way legal anthropological approach can contribute to the development of a field now know as women's studies. What will be explained is the potentiality of yielding rich and valuable data regarding women's issues when the methods developed in anthropological fieldwork are being used in research. The writer illustrate her points by describing her study, conducted in three villages in vicinity of Tarutung, North Sumatera.